CONSIDERATION OF ISLAMIC PSYCHOLOGICAL ASPECTS IN SELECTING AND DEVELOPING SENSITIVE AND CREATIVE LEARNING METHODS IN THE NEW NORMAL ERA CLASSROOM - Mhd. Noor Sitorus; Athiyah Sakinah (Proceeding International Seminar of Islamic Studies, 2021)
In selecting and developing learning methods in the classroom, a teacher is required to be sensitive and creative. By paying attention to students needs and learning objectives, the selection and development of learning methods would be appropriated. Classroom learning in the current era is different from the era before the Covid-19 outbreak. Learning in the classroom after the Covid-19 outbreak is known as learning in the new normal era. The consideration of aspects of Islamic psychology in selecting and developing learning methods in the new normal era is necessary. This study aims to reveal the consideration of aspects of Islamic psychology as a way out in selecting and developing sensitive and creative methods in the new normal era.Keywords: Learning Method; Islamic Psychological Aspects; New Normal Era; Sensitive; Creative